Barriers, Facilitators, and Implementation Strategies of Enteral Nutrition in Critically Ill Children in Pediatric Intensive Care Units: A Scoping Review - Hendrawati, Sri; Maryam, Nenden Nur Asriyani; Permana, Septa (Journal of Nursing Care, 2026)
Enteral nutrition (EN) is the preferred route of nutritional support for critically ill children, yet its implementation in pediatric intensive care unit (PICU) remains challenging. Clinical instability, feeding interruptions, workforce-related issues, and variability in local practices may contribute to optimal EN delivery. This scoping review aimed to map the available evidence on barriers, facilitators, and implementation strategies for EN delivery in critically ill children in PICU and other critical care settings. This review followed the Joanna Briggs Institute methodological framework and was reported in accordance with PRISMA-ScR. Literature searches were conducted in PubMed, Scopus, EBSCOHost, and ScienceDirect for studies published between 2021 and 2026. Eligible studies included primary empirical research involving critically ill infants, children, or adolescents in PICU or pediatric critical care settings that addressed barriers, facilitators, implementation strategies, interruptions, or adequacy of EN delivery. Data were extracted using a structured charting form and synthesised narratively. Ten studies were included. Findings were grouped into three themes: barriers, facilitators, and implementation strategies. Barriers included patient instability, feeding interruptions, limited clinician confidence, inadequate dietitian support, limited feeding resources, and inconsistent documentation. Facilitators included feeding protocols, multidisciplinary collaboration, nursing competency, dietitian involvement, and routine monitoring of nutrition goals. Implementation strategies included standardised EN protocols, quality improvement initiatives, documentation-based interventions, and guideline uptake. EN delivery in critically ill children is influenced by clinical, professional, and organisational factors. The findings suggest that pediatric critical care nursing should prioritise routine monitoring of nutritional goals, early identification of feeding interruptions, adherence to EN protocols, and multidisciplinary collaboration to support more consistent and effective nutritional care in critically ill children. Further PICU specific research is needed to evaluate EN implementation strategies and their clinical outcomes.